Treatment of non-inflamed obstructive meibomian gland dysfunction by an infrared warm compression device. Issue 12 (1st December 2002) - Goto, E; Monden, Y; Takano, Y; Mori, A; Shimmura, S; Shimazaki, J; Tsubota, K
Abstract : Aim: To test the short term efficacy and safety of an infrared warm compression device (IWCD, Eye Hot, Cept Co, Tokyo, Japan) as treatment for non-inflamed meibomian gland dysfunction (MGD). Methods: 37 subjects with non-inflamed obstructive MGD, with and without aqueous tear deficiency (ATD) dry eye, participated in a prospective non-comparative interventional case series. Symptom scores, face scores, tear evaporation rates, fluorescein and rose bengal vital staining, tear break up time (BUT), Schirmer test, meibomian gland obstruction, and meibography were compared before and after 2 weeks of therapy. Results: In a total of 37 cases, total subjective symptom scores and subjective face scores improved significantly, from 12.3 (SD 5.9) to 8.4 (6.1), and from 7.0 (1.7) to 5.3 (2.0) (both p <0.0001). The results for tear evaporation rates during forced blinking (p = 0.002), fluorescein staining (p = 0.03), rose bengal staining (p = 0.03), BUT (p <0.0001), and meibomian gland orifice obstruction score (p <0.0001) had also improved significantly at the end of the 2 week period of infrared thermotherapy. No complaints and/or complications of the IWCD were reported. Conclusion: The IWCD was effective and safe for the treatment of MGD. Improved tear stability associated with release of meibum is a possible mechanism of this treatment.